Use of allyl intermediate in novel synthetic route to rosuvastatin key heterocyclic building block: N-(4-(4-fluorophenyl)-5-formyl-6- isopropylpyrimidin-2-yl)-Nmethylmethanesulfonamide - Čusak, Alen; Časar, Zdenko; Šterk, Damjan (Anali PAZU, 2022)
A key building block of rosuvastatin was prepared via a novel synthetic method. Key feature of the presented synthetic approach is introduction of an allyl group into pyrimidine core at position 5. 5-Allyl substituted pyrimidine derivative can be transformed into title compound in three steps involving izomerisation of the allyl into alkene moiety, oxidation of the alkene moiety to the diol structure and oxidative cleavage of vicinal diol. Synthesis enables preparation of title compound in overall 60 % yield, which represents 88 % average yield per step by applying industrially acceptable reagents and mild conditions.